EFFECTS OF BIFIDOBACTERIUM LACTIS BB12 PROBIOTIC CONSUMPTION ON STREPTOCOCCUS MUTANS LEVELS: A SYSTEMATIC REVIEW OF RANDOMIZED CLINICAL TRIALS - Acuña Ponce de León, Emily Gabriela (2026)
Introduction: One of the main bacteria related to dental caries is Streptococcus mutans, and　currently, various studies are evaluating how to decrease its count. The effect and efficacy of　probiotic consumption as a method to inhibit this bacterium are currently being analyzed.　Objective: To evaluate the effect of the probiotic Bifidobacterium lactis BB12 (BB12) in its different　presentations on Streptococcus mutans (SM) levels in children and adults. Materials and Methods:　An electronic search was conducted in the PubMed, Scopus, EBSCO, and EMBASE databases　to find randomized clinical trials that evaluated the effect of the probiotic BB12 on SM levels.　Results: Studies demonstrated an association between the consumption of BB12 and the reduction　of SM count. Conclusions: Further studies are needed to analyze the effect of the probiotic BB12　on SM, particularly studies investigating larger study populations and conducted over longer study　periods.